PbO2/rGO Electrode as a Superior and Efficient Anode in Electrocatalytic Degradation of Safranine-O - Aryani, Titin; Roto, Roto; Mudasir, Mudasir (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
The electrocatalytic degradation method with PbO2/rGO electrode (anode) was chosen to treat Safranine-O waste because it was cheap and environmentally friendly. This research aimed to study the electrocatalytic efficiency of PbO2/rGO working electrode in Safranine-O removal. In this research, rGO and PbO2/rGO electrodes were synthesized and applied to Safranine-O removal through electrochemical degradation. The characterization results of the morphology of rGO are in the form of a layered structure and have the atomic composition of C (82.87%) and O (17.13%). The characterization results of PbO2/rGO are uniform particles with gaps/pores that appear relatively large. The rGO particles in the form of sheets (layers) seem to be distributed on the surface of PbO2.  PbO2/rGO electrode has the atomic composition of C (87.24%), O (9.03), and Pb (3.73). The application of PbO2/rGO anode to the electrochemical degradation of Safranine-O showed good performance. It was able to perform dye removal (DE%), as well as a decrease in BOD and COD values up to >95% within 10 minutes at a concentration of 20 ppm. Application on real waste also showed the ability of dye removal, COD, and BOD reduction up to >95%. Coating or modifying the PbO2 anode with rGO can reduce the dissolution of Pb2+ ions in the solution during the electrochemical degradation. This study concluded that the PbO2/rGO electrode has improved the efficiency in Safranine-O degradation. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).